COMBINING ABILITY ANALYSIS FOR YIELD AND RELATED TRAITS IN RICE (ORYZA SATIVA L.) - MALIK, SHILPI; SINGH, SURENDRA (The Bioscan, 2013)
Combining ability study on grain yield and component traits from a line x tester analysis of 20 lines, 2 CMS & 1 TGMS testers and 60 crosses, indicated non additive gene effects were predominant for all the traits viz. Days to 50% flowering, plant height, panicle length, panicle number per plant, tiller per plant, panicle weight, 1000 grain weight, spikelet number per panicle, grain number per panicle, % spikelet fertility and harvest index. Amongst parents PUSA 6A (T3) in testers and UPR 3456-4-2-2 (L14) in lines are good combiners for grain yield and other yield related component traits based on their GCA effects. Top hybrids expressing highest SCA effects for grain yield were obtained with general combiners involved into different parental combinations of UPR 3403-41-1 x UPRI 95-167 (L1 x T1), UPRI 2008-62 x UPRI 95-17A (L20 x T2) and UPR 3428-4-1-1 x UPRI 95-17A(L11 x T2). Two lines viz. UPR 3456-4-2-2 (L14) and UPR 3434-1-1-2 (L12) were identified as good general combiners based on their mean performance and GCA effects for yield and its various traits. These crosses may be exploited for commercial cultivation besides the possibility of isolating transgressive segregants from their segregating generations.